Introduction to Cross-Cultural Management Issue - Dymsza, William A.; Negandhi, Anant R. (Journal of International Business Studies, 1983)
Early in 1982, the Editor-in-Chief of JIBS decided to publish a special issue on cross-cultural management at the suggestion of Professor Nancy Adler of McGill University, following her successful organization of the symposium at her university. Professor Anant R. Negandhi was approached and agreed to be a guest editor. Papers included in this issue are the result of this endeavor.